Formulation Of Nickel Matrix Composite Coating Utilizing Malaysian Quarry Dust As Reinforcement For Tribology And Corrosion Performance - Othman, Intan Sharhida; Othman, Radzali; Mohamad Juoi, Jariah; Sundi @ Suandi, Syahrul Azwan; Mohd Rosli, Zulkifli; Zainal Abidin, Muhammad Zaimi (UTeM, 2020)
Quarry industries in Malaysia plays a significant and essential role in the development of the country. However, the enviromental concern is currently rising as one of the main challenging issues affecting the natural aggregate and limestone production. According to Sridharan et al. (2006), about 20- 25% of total production in each crusher unit is left out the quarry dust as waste material. Therefore, efforts have been taken to control enviromental pollution arising due to disposal of these industrial wastes by converting them into utilizable raw materials for usable application. Quarry dust is one of the by- product from the crushing process during quarrying activities, which have gained attention to be used for various applications. Recently, the utilization of quarry dust which is high in silica and alumina content have been extended to be used as a reinforcement for metal matrix composites due to high cost of conventional ceramic particles. Therefore, the effect of various compositions of quarry dust on the tribological and hardness properties of nickel matrix composite coatings electrodeposited on tungsten carbide substrate was investigated in this study. This research will contribute to the knowledge on the improvement of tribological and hardness of nickel-quarry dust composite coating electrodeposited on tungsten carbide via various compositions of quarry dust. The findings would be benefited by the cutting tools industries.